Perbedaan Pengaruh Terapi Napas Dalam dan Terapi Relaksasi Otot Progresif terhadap Penurunan Tekanan Darah Lansia Hipertensi di Posyandu Lansia Kelurahan Surau Gadang Kecamatan Nanggalo Padang Tahun 2012 : The Difference Between the Effects of Deep Breath Therapy and Relaxation Therapy Progressive Muscle on Reducing Blood Pressure in the Elderly with Hypertension at the Elderly Posyandu Surau Gadang Village Nanggalo Padang District in 2012 - Melda Yulinda; Lili Fajria (NERS Jurnal Keperawatan, 2013)
Hypertension is a disease that affects many elderly. Non-pharmacological management is recommended to avoid the effects of pharmacological treatment in the elderly. It can be performed by a deep breathing and progressive muscle relaxation therapy. Breathing can stimulate the release of nitric oxide to dilate the blood vessels so that blood pressure can be lowered. Progressive muscle relaxation therapy can decrease sympathetic nerve activity that causes vascular vasodilatation so that blood pressure lowered. The purpose of this study was to determine the difference in therapeutic effect of deep breathing and progressive muscle relaxation therapy for hypertensive elderly blood pressure reduction. This study used a quasi experimental design with non-equivalent approach Comparison Group Pretest-Posttest Design using a paired t test, unpaired t test and Man-Whitney test. Total sample of 30 respondents dispersed 15 people got a deep breath therapy and 15 received progressive muscle relaxation therapy. The results showed that there were reductions in blood pressure in each group with p = 0.000 and there are differences in blood pressure reduction between treatment groups deep breath and progressive muscle relaxation therapy with p = 0.001 and p = 0.042 systolic. Progressive muscle relaxation therapy better at lowering blood pressure in the elderly. It is recommended to perform progressive muscle relaxation for the Nonpharmacologic treatment of hypertension in older adults with hypertension.